Using a Participatory Approach to Develop Research Priorities for Future Leaders in Cancer-Related Precision Public Health - Roberts, Megan C.; Mader, June Mullaney; Turbitt, Erin; Smit, Amelia K.; Landry, Latrice; Olstad, Dana Lee; Passero, Lauren E.; Allen, Caitlin G. (Frontiers in Genetics, 2022)
Precision public health is an emerging discipline combining principles and frameworks of precision health with the goal of improving population health. The development of research priorities drawing on the strengths of precision and public health is critical to facilitate the growth of the discipline to improve health outcomes. We held an interactive workshop during a virtual conference bringing together early-career researchers across public health disciplines to identify research priorities in precision public health. The workshop participants discussed and voted to identify three priority areas for future research and capacity building including 1) enhancing equity and access to precision public health research and resources, 2) improving tools and metrics for evaluation and 3) applying principles of implementation science to support sustainable practices. Participants also developed future objectives for achieving each priority. Future efforts by working groups will continue the process of identifying, revising, and advancing critical research priorities to grow the impact of precision public health.